Rhizosphere Bacteria Increased the Height and Root Number of Chili Plants (Capsicum annuum L.) - Anjani, Nofa; Rahayu, Triastuti; Sidiq, Yasir (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
The need for potential bacteria as plant-promoting agents is still in high demand. Previous reports suggested five potential rhizobacteria isolated from the frangipani plant (Pulmeria accuminata) and producing indole acetic acid (IAA). However, evidence of its potential as a plant growth promoter has not been obtained. Therefore, this study aims to test the effect of rhizosphere bacterial inoculation on chili plants (Capsicum annuum L.). The method was a quantitative experimental method, with 15 repetitions for each treatment. The data were analyzed using a 95% student t-test confidence test or a significant level of 5% (a = 0.05). This inoculation begins with the germination of chili seeds until the radicula is observed. The germinated chili seedlings were soaked in bacterial suspension for an hour at room temperature. The results showed that inoculation using P38 isolate incubated for 6 hours significantly increased plant height and number of roots. The P31 isolate that was incubated for 6 hours inhibited the height of plants and the number of leaves of chili plants. Thus, these results provide important information about the effect of inoculation of newly isolated rhizosphere bacteria.